Discriminatory Discipline: Trends and Issues. (June 2016) - Whitford, Denise K.; Katsiyannis, Antonis; Counts, Jennifer
Discriminatory discipline has been widely documented for decades, yet little progress has been made to narrow the gap. Due to the long-standing history of discriminatory discipline, current nationwide data, and recent federal initiatives, there is a need for a comprehensive examination of this critical issue. Therefore, we discuss populations effected by discriminatory discipline, including students of color and students in special education. Research indicates that prevention and intervention efforts that begin at the administrative level are necessary.